Pengaruh sistem bagi hasil terhadap kesejahteraan petani padi dari konsep Mudharabah di Kecamatan Sanrobone - Mita Ariani; Idham Khalid; Sri Wahyuni (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the effect of the profit-sharing system on the welfare of rice farmers from the mudharabah concept in Sanrobone District. The background of this study is that many farmers do not have farming skills, as well as landowners who are unable to manage their own land. The method used is a quantitative method with a descriptive approach. Data collection was carried out through questionnaires to 96 respondents selected using the purposive sampling method. Data were analyzed using simple linear regression tests, validity tests, reliability tests, and classical assumption tests such as normality and heteroscedasticity. The results of the study showed that the profit-sharing system had a significant effect on farmer welfare. This is indicated by increasing income, access to education and health services. The conclusion of this study is that the application of a profit-sharing system based on the mudharabah concept can improve farmer welfare. Keywords: Profit-Sharing System, Mudharabah, Farmer Welfare.